Enhancing Permeation of Drug Molecules Across the Skin via Delivery in Nanocarriers: Novel Strategies for Effective Transdermal Applications - Yu, Yi-Qun; Yang, Xue; Wu, Xiao-Fang; Fan, Yi-Bin (Frontiers in Bioengineering and Biotechnology, 2021)
The transdermal route of administration provides numerous advantages over conventional routes i.e. oral or injectable for the treatment of different diseases and cosmetics applications. The skin also works as a reservoir, thus deliver the penetrated drug for more extended periods in a sustained manner. It reduces toxicity and local irritation due to multiple sites for absorption and owes the option of avoiding systemic side effects. However, the transdermal route of delivery for many drugs is limited since very few drugs can be delivered at a viable rate using this route. The stratum corneum of skin works as an effective barrier, limiting most drugs' penetration posing difficulty to cross through the skin. Fortunately, some non-invasive methods can significantly enhance the penetration of drugs through this barrier. The use of nanocarriers for increasing the range of available drugs for the transdermal delivery has emerged as a valuable and exciting alternative. Both the lipophilic and hydrophilic drugs can be delivered via a range of nanocarriers through the stratum corneum with the possibility of having local or systemic effects to treat various diseases. In this review, the skin structure and major obstacle for transdermal drug delivery, different nanocarriers used for transdermal delivery, i.e., nanoparticles, ethosomes, dendrimers, liposomes, etc., have been discussed. Some recent examples of the combination of nanocarrier and physical methods, including iontophoresis, ultrasound, laser, and microneedles, have also been discussed for improving the therapeutic efficacy of transdermal drugs. Limitations and future perspectives of nanocarriers for transdermal drug delivery have been summarized at the end of this manuscript.